Tunable Bandgap Engineering of Zn x Cd1−x Se Solid Solution with Controlled Ratio via a Facile One‐Pot Synthesis for Visible‐Light Photocatalytic H2 Production - Lin Wei (Advanced Energy & Sustainability Research, 2022)
Metal selenide semiconductors in photocatalysis are limited, owing to their low activity and poor stability. Herein, a facile one‐pot solution approach is developed to prepare particulate Zn x Cd1−x Se solid solutions with tunable energy band structures. X‐ray diffractometer (XRD) patterns demonstrate that the crystal structure of the samples are not changed. The analysis of UV–vis and the photoluminescence spectra exhibits that the bandgap of Zn x Cd1−x Se photocatalysts utilizing oleylamine as an organic template can be accurately controlled, which gradually becomes wider from 1.60 to 2.70 eV with increasing Zn/Cd molar ratio. Under visible‐light irradiation, the optimal Zn0.5Cd0.5Se without any cocatalyst exhibits a superior photocatalytic H2 generation rate (438.3 μmol h−1 g−1), exceeding that of pristine CdSe and ZnSe by more than 12 and 17 times, an apparent quantum yield of 1.7% at 420 nm and excellent stability. The results are on account of the balance between the bandgap width and the conduction band (CB) potential of Zn0.5Cd0.5Se, implying the excitation of more photogenerated electrons and faster charge carrier separation efficiency, which could be substantiated by the transient photocurrent response and electrochemical impedance spectroscopy. Therefore, this work provides a straightforward strategy to synthesize metal selenide for diverse photocatalytic applications.